Application Development Android-based Tourism Case Study of North Sulawesi Province - Jimmy Robot (East Asian Journal of Multidisciplinary Research, 2023)
North Sulawesi Province, which is often called North Sulawesi, is a province located at the northern tip of Sulawesi Island. North Sulawesi has 11 regencies and 4 cities and Manado City is the capital of this province. Based on Law Number 13 of 1964, on August 14, 1959 the North Sulawesi Province was formed so that day was determined as the anniversary of the Province. Some areas in Sulawesi North is also a barometer of national tourism development. The tourism sector has become a mainstay sector not only for the provincial government, but also for the participation of all layers of society. Technological developments that are increasing rapidly can now cover all fields, one of which is in the field of Information Systems such as the Android application which has been used to display tourist information and tourism support facilities such as hotels, transportation, souvenir shops, and other things. To make things easier, Android also provides access and integration with the Google Maps service. The process of making this application uses the Rapid Application Development (RAD) method which consists of 3 phases, namely Requirements Planning, RAD Design Workshop, and Implementation. For the continued development of the Android-based Tourism Location Based Service application in North Sulawesi Province by adding other features that are more supportive.